Long-term consumption of Western diet contributes to endothelial dysfunction and aortic remodeling in rats: Implication of Rho-kinase signaling. (17th February 2019) - Elrashidy, Rania A.; Zhang, Jing; Liu, Guiming
ABSTRACT: Western diet (WD), rich in saturated fat and sugars, has become a risk factor for obesity and metabolic syndrome, however, its effect on endothelial function and vascular remodeling is not fully elucidated. Recent evidence suggests cross-talk between Rho kinase (ROCK) pathway and cardiovascular system. We aimed to investigate the effect of WD on aortic remodeling and the contribution of ROCK signaling. Eight week old male Sprague-Dawley rats were fed either standard chow diet (SD) or high fructose/ high-fat diet, typically as in WD. After 42 weeks, WD-fed rats showed hyperglycemia, dyslipidemia, and hypertension without marked weight gain, compared to SD-fed rats. Significant up-regulation of ROCK-1 and −2, along with a decline in eNOS expression were found in the aortic tissue of WD-fed rats. Additionally, WD-fed rats displayed oxidative stress and fibrosis in their aortic tissues versus controls. Our findings suggest that long-term feeding of WD contributes to endothelial dysfunction and aortic remodeling in adult male rats. ROCK activation seems to be involved in WD-related vascular disorders and may represent a promising therapeutic target.